Cupcake Bakesolutely Business Plan - Wangsa, Mega (Devotion : Journal of Research and Community Service, 2022)
Bakesolutely Cupcake business plan is the author's new plan in the food sector that offers various types of Cupcakes that are processed using natural colors and flavors. In general, colors are divided into two types, natural colors, and synthetic colors. Several factors support the use of synthetic colors, some are using it to reduce production costs. Like a cupcake in general, Bakesolutely Cupcakes can be part of various kinds of celebrations. This business plan was chosen to see the many opportunities that can be taken where every time around us, there is always a special day, support for a healthy lifestyle, and supported by the hobby of the writer. This research uses a qualitative method with an ethnographic approach and a case study. Netnography is a research method that is carried out online to collect digital artifacts in the form of available records regarding a matter. Based on the results from various perspectives that have been designed, Bakesolutely's cupcake business plan is feasible to run.